A concepção de ensino sob medida na obra hygiene mental e educação (1927), de Luiz Antônio dos Santos Lima - Silva, Juliana da Rocha e (2013)
This dissertation examines the concept of the personalized teaching proposed by the physician and educator from Rio Grande do Norte Luiz Antonio dos Santos Lima, in his doctoral thesis "Mental Hygiene and Education," published in 1927. To do so, we start from the assumption that this thinker appropriated part of the educational theory formulated by Èdouard Claparède - specifically, in the case of the teaching concepts of the personalized teaching and comprehensive education designed by the Swiss intellectual - and, considering the Brazilian social reality of early twentieth century, reframed these concepts, adapting them to the country context. To implement the proposed idea, the bibliographical study was the option chosen, and so was done through a theoretical research which had as a reference authors whose studies referred to the Brazilian historical moment in the late nineteenth and early twentieth century, our examined time frame. As for the understanding and the methodological analysis of discourse, seen as socially constructed, the Foucault postulations were studied under an analytical approach, in which the disciplinary society is analyzed from the relations of power and knowledge that exist in it. The main source of this research was the work of "Mental Hygiene and Education," published as a requirement to the obtainment of Luiz Antonio s medical degree by the Rio de Janeiro Medicine School. Thus, it was found that the conception of personalized learning to the comprehensive education of students, as proposed in the doctoral thesis of Luiz Antonio dos Santos Lima, was related to abnormalities of mental character that children could present. School education was thought in a way by the potiguar thinker that it could be applied as deep as the moral, intellectual and behavioral deviations of the individual were, making use of hygiene practices of the minds through a normalizing process towards a civilized and developed future of the Brazilian nation which would manage, watch and fix the thoughts of the school students